Using Google AdWords and AdSense - Miller, Michael (Que, 2010)
Using Google AdWords and AdSense brings you over 75 video tutorials and audio sidebars detailing everything from AdSense for mobile content and determining your AdWords budget to creating effective ads and choosing the right keywords. Watching these media elements is the fastest way to get started as either an ad host or an advertiser. Topics covered include making money with AdSense, affiliate advertising, performance monitoring, increasing AdSense revenue, using the Traffic Simulator tool, advertising on YouTube, and much, much more!